Towards a sustainable future in the age of polycrisis - Siirilä, Jani; Salonen, Arto O. (Frontiers in Sustainability, 2024)
Our generation lives in an age of polycrisis. Polycrisis is a phenomenon where various single crises interact in ways that lead to an overall negative impact that is more significant than the sum of each issue. The age of polycrisis poses a considerable threat to humanity. Since the age of polycrisis results from human actions, humans are responsible for addressing it. As such, an ultimate roadmap and in-depth sustainability transformations are needed across all sectors. This raises a quest for a unified social contract that can engage everybody to promote the well-being of people and the planet locally, regionally, and globally. Our paper explores a holistic picture of a social transformation process to address the challenges of the age of polycrisis. We put together a new social contract, different actors (civic society, private sector, public sector, decision-makers), and specific focus areas of actors to implement the goals of Agenda 2030. Each societal sector has a unique role to play in this transformation. The private sector can drive innovation and investment, the public sector can provide governance and regulation, civic society can advocate for change and hold other sectors accountable, and decision-makers can provide leadership and coordination. A new social contract called “Society’s Commitment to Sustainable Development” can foster societal transformation towards sustainability with the involvement of these different societal sectors. The widespread commitment of public and private sectors as well as civil society can be an effective driver when implementing Agenda 2030 goals to build a more sustainable future. We, the current generation, have power to make a difference regarding international collaboration, national decision-making, industries, households – even down to the choices we make in our everyday lives. The future is shaped by the decisions we make today.